Strengthening Islamic Education Learning Outcomes through The Discovery Learning Model - Sutanto; Jazilurrahman (EDUCARE: Jurnal Ilmu Pendidikan, 2024)
This study aims to explore the application of the Discovery Learning model to enhance learning outcomes in Islamic Education. The research adopts a qualitative case study approach. Data collection methods include participant observation, in-depth interviews, and documentation, analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The findings demonstrate that the implementation of the Discovery Learning model positively influences multiple aspects of learning. These include the redesign of the Islamic Religious Education curriculum, intensive teacher training, structured lesson planning, and application of Higher Order Thinking Skills (HOTS)-based assessments. Notably, student participation transformed from passive to active, with marked improvements in critical thinking, learning motivation, understanding of religious concepts, and assessment outcomes. Around 80% of students showed enhanced motivation and engagement, and assessment results improved by approximately 20% compared to traditional methods. The implications of this study emphasize that Discovery Learning fosters not only cognitive mastery but also independent exploration and contextual application of Islamic teachings. This student-centered model bridges theoretical knowledge with real-world practice, making Islamic Education more relevant and impactful. However, its success is contingent on teacher readiness and continuous professional development. The research suggests that broader implementation across various educational institutions could contribute significantly to modernizing religious education practices in Indonesia.